(untitled) (World Bulletin of Education and Learning, 2025)
In this article, pedagogical approaches to the development of the modern system of training of personnel in the conditions of the New Uzbekistan are scientifically-theoretically analyzed. It highlights the role and importance of competency, personality-oriented, innovative and integrative educational approaches in the educational process. Issues of training of competitive, creative and socially responsible personnel are also revealed through the introduction of digital technologies in the educational system, the development of critical thinking, the implementation of the principles of continuing education. The results of the study serve to develop practical recommendations aimed at improving pedagogical approaches and improving the quality of Education.